Effects of Spouse Deployment on Pregnancy Outcomes: A Prospective Cohort of a Military Population [20]. (May 2015) - Tarney, Christopher; Berry-Caban, Cristobal; Jain, Ram; Kelly, Molly; Sewell, Mark; Wilson, Karen
Abstract : OBJECTIVE: To evaluate the effects of spousal deployment to a combat zone during the antenatal period on maternal and neonatal outcomes. METHODS: Primigravid women who delivered at Womack Army Medical Center, Fort Bragg, were prospectively enrolled in the study between January 2013 and January 2014. Women whose spouses were deployed to a combat zone during the pregnancy (deployed group) were compared with women whose spouses were not deployed at all during the pregnancy (nondeployed group). Pregnancy and neonatal outcomes were compared between the two groups. RESULTS: A total of 397 women were enrolled, with 183 in the deployed group and 214 in the nondeployed group. Compared with those in the nondeployed group, women in the deployed group were at increased risk for preterm delivery ( P <.001), severe preeclampsia ( P =.049), and postpartum depression ( P =.001). Women in the deployed group who participated in group prenatal care were less likely to have preterm delivery (14.6% compared with 22.5%) and postpartum depression (9.8% compared with 18.3%) when compared with those in traditional prenatal care. CONCLUSION: Pregnant women who have a spouse deployed during their pregnancies may be at increased risk for preterm birth, severe preeclampsia, and postpartum depression. When spouses are deployed, group prenatal care may have a positive effect on preterm delivery and postpartum depression.